Understanding the friction and deformation behavior of micro/nano-hierarchical textures through in-situ SEM observation and mechanics modeling. (January 2022) - Afshar-Mohajer, Mahyar; Yang, Xingwei; Long, Rong; Zou, Min
Abstract: Micro/nano-hierarchical textures play essential roles in realizing the functionalities of surfaces. Their friction and deformation behavior at the nanoscale, although important, are relatively unknown. In this study, through targeted friction tests inside a scanning electron microscope of individual micro/nano-hierarchical structures (micropillars covered with nanohairs) fabricated by two-photon lithography, we discovered the coupling between micropillar deformation and nanohair height. We also found that the bending of long nanohairs can provide assistive sliding forces, and lateral force can develop even under just normal load before sliding due to the buckling of the longer nanohairs. These findings, supported by finite element modeling of the tests, will shed light on the design of novel micro/nano-hierarchical textures to realize deformation-resistant functional surfaces with controlled friction. Graphical Abstract: ga1 Highlights: Micro/nano-hierarchical textures were fabricated via two-photon lithography. Hierarchies consisted of nanopillars of different heights on top of micropillars. Effect of nanopillar height on trapped air and thus wettability was uncovered. In-situ SEM tribological testing of hierarchical structures was carried out. The coupling between friction and deformation was directly observed and modeled.